Pengaruh Konsistensi, Disiplin Kerja, Jujur, Bertanggung Jawab, Kreatif dan Orientasi Masa Depan terhadap Tingkat Pendapatan (Study Case on Young Moslem Entrepreneur in IAIN Salatiga) - Musalim Ridlo (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2020)
This study aims to identify and analyze the influence of consistency, work discipline, honest, responsible, creative and future orientation towards the level of income. This type of research used in this study is a quantitative approach. The variables used are work discipline, honesty, consistency, creative, future orientation, responsibility (independent) and income level variables (dependent). Data collection techniques in this study using a questionnaire given to respondents through the google form application. Then the data obtained were tested with multiple regression models through the application of SPSS version 16. The results of this study indicate that work discipline variables have a significant positive effect on the level of opinion, honest variables have a significant positive effect, consistency variables have a significant positive effect, future orientation variables have a negative effect not significant, the responsibility variable has a significant positive effect. And simultaneously the independent variable significantly influence the level of income (dependent).